KIRI ISLAM HASAN HANAFI - Akso, Akso; Faridah, Faridah (Moderation | Journal of Islamic Studies Review, 2023)
Islam is a praxis that seeks to dismantle oppressive and discriminatory social order. It is in this context that Islamic theology has always been synonymous with liberation theology. Hasan Hanafi used leftist Islam in the context of a social structure in which there were two opposing social classes. The first class, the established elite class (right class). It controls both the means of production and the means of political power, and seeks to exploit other classes. The other class, the majority, (the left). In such a social order, the Islamic left is meant to defend the interests of the majority in order to restore the rights of the poor from the rich, to defend the weak in the face of the strong, and to make humanity all equal. Even today the social order still reflects clashes between the elite and the majority. For this reason, liberation theology is still relevant to apply.